2010
DOI: 10.1158/0008-5472.sabcs10-p3-10-21
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P3-10-21: Audit of the Accuracy of Immunohistochemical (IHC) Testing of HER2 Status of Breast Cancer in the United Kingdom: An Interim Analysis

Abstract: Background: The analysis of the level and distribution of HER2 protein expressed by cancer cells (HER2 status) is of great clinical value in the management of breast cancer patients both for the determination of the prognosis of disease and for identification of those patients who are eligible for anti-HER2 therapy. Accurate assessment of the HER2 status is essential for identifying patients which will benefit from HER2 targeted therapy. HER2 status in the UK is established using a two tier strategy with IHC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…At pathological level, there are emerging data to suggest that at least some of the observed discordance may be owing to an inappropriate selection of patients who could benefit from antiHER2 treatments. Cumulative worldwide experience gained over a decade of HER2 testing of breast cancer patients has suggested that a subset of patients scoring negative (score 0, 1+) may show gene amplification ( Dendukuri et al , 2007 ; Starczynski et al , 2010 ; Iorfida et al , 2012 ; Brunello et al , 2013 ). This has led to the need for an alternative way of interpreting such discordances ( Starczynski et al , 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…At pathological level, there are emerging data to suggest that at least some of the observed discordance may be owing to an inappropriate selection of patients who could benefit from antiHER2 treatments. Cumulative worldwide experience gained over a decade of HER2 testing of breast cancer patients has suggested that a subset of patients scoring negative (score 0, 1+) may show gene amplification ( Dendukuri et al , 2007 ; Starczynski et al , 2010 ; Iorfida et al , 2012 ; Brunello et al , 2013 ). This has led to the need for an alternative way of interpreting such discordances ( Starczynski et al , 2012 ).…”
Section: Discussionmentioning
confidence: 99%